BIOGRAFISKE SAMLINGER: Subjektivitet, identitet og materielle livshistorier - Otto, Lene (Tidsskriftet Antropologi, 2001)
The article is approaching the sensory and the material, memory and private reminiscence, objects and time from the perspective of ethnology. It is an attempt to provide an understanding of the relation between people and objects in a biographical perspective. It is argued that the act of keeping and saving is a kind of technology of the self. Biographical objects, because of their materiality and sensory qualities constitute our picture of our own past, stimulate remembering, store information beyond individual experience, and are instrumental to the formation of consciousness and identity. Biographical collections are the result of saving, not just casual keeping of objects connected with a person’s own life history. Thus, they are material life stories.